How to Improve Learning Outcomes of the Indonesian Language in Elementary Schools through the Implementation of Problem-Based Learning Methods - Salam, Salam; Firman, Firman; Mirnawati, Mirnawati (Institut Agama Islam Negeri Palopo, 2022)
This study aims to improve Indonesian language learning outcomes through problem-based learning in class V SD Negeri Panciro, Bajeng District, Gowa Regency. This Classroom Action Research (CAR) uses two cycles, each of which is carried out in four actions. This study involved 24 students and a classroom teacher who acted as collaborators. The results showed that each passed cycle tended to increase student learning outcomes. Based on the research findings, it can be concluded that using problem-based learning models can improve the learning outcomes of fifth-grade students at SD Negeri Panciro Kec. Bajeng Kab. Gowa on the material ‘Information.’ It can be seen from the first cycle results that the total score achieved was 59, while in the second cycle, the number of student achievements increased to 89 or very good criteria. In addition, there was a significant increase from 59 to 89. Therefore, to improve the quality of Indonesian language learning, this learning method could continue to be developed in learning activities in schools. The problem-based learning method can be used as an alternative learning option to improve student learning outcomes.